The Public Records of the Colony of Connecticut, Prior to the Union with New Haven Colony, May, 1665 (1850) Page 113-114 - (:unkn) unknown (General Publisher, 1665)
Prohibited selling or trading “to the Indeans,” nor any Dutch or Frenchman any guns, pistols, and other warlike instruments. Violators fined “twenty for one” and corporal punishment at the court’s discretion.
--
Keywords: TRANSFER